2019
DOI: 10.2147/ijn.s198376
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pulmonary toxicities from a 90-day chronic inhalation study with carbon black nanoparticles in rats related to the systemical immune effects</p>

Abstract: Background: Recent years, there occurs heavy haze pollution in northern China during wintertime. The potential influence of airborne particulate matter (PM) on human health attracts great concern. The fuel-derived PM in the inhalable size range is dominated by aggregates of nanoparticles of Carbon black (CB). However, there are still lack of evidences especially regarding long-term exposure to explain the chronic effects of nanoscaled CB and the relative mechanism. Purpose: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 44 publications
0
30
0
2
Order By: Relevance
“…Our pilot studies, designed to explore FDNP-(NV) distribution in rat organs upon both short- and long-term exposure,7,8 demonstrated principle deposition of particles in the liver with secondary deposition to the spleen while other organs shared only a minor fraction. Interestingly, the large deposit of FDNP-(NV) in the liver 5 days after exposure remained unchanged in the 14-days and 12-weeks post-exposure studies 7,8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our pilot studies, designed to explore FDNP-(NV) distribution in rat organs upon both short- and long-term exposure,7,8 demonstrated principle deposition of particles in the liver with secondary deposition to the spleen while other organs shared only a minor fraction. Interestingly, the large deposit of FDNP-(NV) in the liver 5 days after exposure remained unchanged in the 14-days and 12-weeks post-exposure studies 7,8…”
Section: Introductionmentioning
confidence: 99%
“…Our subsequent rodent POC (efficacy) studies raised an important caveat, ie, anatomical considerations suggest that recording NIR from locales within the body pose challenges associated with opacity and auto-fluorescence in an organ- and tissue-dependent manner 7. To optimize NIR signal captured from within the body in a location such as the carotid artery (in humans, 15–20 mm from skin surface), we have selected larger nanodiamond particles: FNDP-(NV)-Z-average~800 nm, a strain of particles that possess superior NIR emission (650~720 nm) over smaller particles of the same strain as well as over the NVN “color center” strain 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient aqueous solubility is one of the essential requirements for oral administration of a drug. Limited solubility can lead to insufficient dissolution and further reduce the bioavailability of a drug 7,8. As a result, a variety of effort has been made to enhance the oral bioavailability of poorly water soluble drugs through lipid based emulsion systems, specifically the self-emulsifying drug delivery system (SEDDS) 912.…”
Section: Introductionmentioning
confidence: 99%
“…As nanotechnology may facilitate ocular drug delivery,38,39 we constructed IL-12-PNP for the topical application and sustained release of IL-12. In addition, PLGA protects proteins against degradation and stabilizes their structure 40. We demonstrated that IL-12-PNP furnished sustained release of IL-12.…”
Section: Discussionmentioning
confidence: 80%